PENGARUH KEPERCAYAAN DAN KUALITAS PELAYANAN TERHADAP KUNJUNGAN PASIEN KEMBALI DENGAN KEPUASAN PASIEN SEBAGAI VARIABEL INTERVENING PADA RUMAH SAKIT PGI CIKINI JAKARTA - Alphinus R Kambodji (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2022)
This study aimed to analyze the Effect of Trust and Quality of Service on Return Patient Visits with Patient Satisfaction as Intervening Variables at PGI Cikini Hospital Jakarta. The study respondents were hospitalized patients of PGI Cikini Hospital with as many as 225 people using purposive sampling techniques. Data collection uses questionnaires, and data is processed using descriptive quantitative and path analysis. Study conclusion: (1) Trust has a direct effect on return patient visits; (2) Quality of service directly affects patient visits; (3) Trust has a direct effect on patient satisfaction; (4) Quality of service directly affects patient satisfaction; (5) Patient satisfaction directly affects the patient's return visit; (6) Trust affects return patient visits through patient satisfaction as intervening variables; (7) The quality of service affects patient visits again through patient satisfaction as intervening variables.